KOŠARE AS A GEOPOLITICAL AND GEOIDENTITY PARADIGM - Stepić, Milomir (Political Review, 2025)
NATO’s aggression against the FRY in 1999 for the purpose of the violent “amputation” of the Kosovo-Metohija province of Serbia had far-reaching implications. This applies not only to the regional, i.e. ex-Yugoslav and Balkan framework, but also to a much broader, European and global plain. Serbian defense – especially to stop the land penetration in the area of the Košare border crossing – became an example that resistance to the strongest world power and military alliance in history is, after all, possible. Košare became a multidimensional symbol: of protection of the state border, defense of the geopolitical core of the Balkans, opposition to Greater Albanian expansionism and of a new confrontation between the great powers. Moreover, Košare, as well as the entire “Kosovo precedent”, became a paradigm of the peak of unipolarism, but soon also a litmus test of global changes that would bring about the decline of American (all)power and the multipolarization of the world order. From the “Serbian point of view”, Košare was engraved in the national “mental map” and culture of memory as a turning point in the “New Battle of Kosovo” and an additional, contemporary element of the eternal Kosovo Covenant. Due to its objective importance in the defense of the country, the symbolism of confronting an incomparably stronger attacker and the demonstrated heroism of the few Serbian soldiers, Košare was rightly called the “Serbian Thermopylae”.
Keywords: multiple symbolism; “Serbian Thermopylae”; border; Balkan core; “geopolitical macro-fortress”; Greater Albanian expansion; Kosovo and Metohija